2015
DOI: 10.1016/j.memsci.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A new multimodal membrane adsorber for monoclonal antibody purifications

Abstract: This contribution describes research on the use of a newly developed multimodal membrane (MMM) adsorber that can be used as a chromatographic stationary phase in bioseparation processes. Compared with commercial cationic multimodal adsorbers, this MMM has superior static binding capacity (SBC = 180 mg IgG/ml), dynamic binding capacity (DBC 10% = 60 mg IgG/ml), and load productivity (>10 mg/ml/min). Furthermore, the incorporation of functional groups that provide orthogonal modes of interactions increases the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…The difference between DBC and equilibrium binding capacity is much more significant for the MMM than for Protein A HP resin. Previously we found that the binding reaction for this MMM is relatively slow and might possibly originate from the hydrophobicity of the ligands, which affects both the polymer conformation and the number of easily accessible binding sites . It appears that over time as protein binds within the polymer layer, it swells and provides access to additional binding sites, resulting in high equilibrium capacities.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The difference between DBC and equilibrium binding capacity is much more significant for the MMM than for Protein A HP resin. Previously we found that the binding reaction for this MMM is relatively slow and might possibly originate from the hydrophobicity of the ligands, which affects both the polymer conformation and the number of easily accessible binding sites . It appears that over time as protein binds within the polymer layer, it swells and provides access to additional binding sites, resulting in high equilibrium capacities.…”
Section: Resultsmentioning
confidence: 93%
“…The volumetric flow rate was 1 CV/min (1 min residence time). Much shorter residence times could be used for the membrane column, as we have demonstrated . A 1 min residence time was selected for comparison of the columns so that the Protein A column would have sufficient binding capacity, as its capacity decreases with increasing flow rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations